EFFECT OF ECONOMIC GROWTH, REGIONAL GENUINE REVENUE, GENERAL ALLOCATION FUNDS, AND SPECIAL ALLOCATION FUNDS ON CAPITAL EXPENDITURE (STUDY ON DISTRICT/CITY LOCAL GOVERNMENTS IN CENTRAL JAVA PROVINCE, 2015-2019) - Salma Meirani Utami; Zuhrohtun Zuhrohtun; Januar Eko Prasetio (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research aims to examine the effect of economic growth, regional original income, general allocation funds, and special allocation funds on capital expenditure. The type of data collected is secondary data obtained from Badan Pemeriksa Keuangan the Central Statistics Agency. The sampling technique uses a non probability sampling method that produces a sample of 175 data from 35 regencies/ cities in Central Java in 2015-2019. The analysis technique used in this study is multiple linear regression analysis using the SPSS application. The results of statistical tests show that the regional income, general allocation fund and the special allocation fund have an effect on the capital expenditure, while the economic growth has no effect on the capital expenditure.